A functional ruthenium(ii) complex for imaging biothiols in living bodies1. Issue 17 (7th May 2015) - Ye, Zhiqiang; Gao, Quankun; An, Xin; Song, Bo; Yuan, Jingli
<x xml:space="preserve">Abstract</x> A functional ruthenium(ii) complex that can act as a luminescent probe for imaging biothiols in living bodies has been successfully developed.